2009
DOI: 10.1108/02652320910928245
|View full text |Cite
|
Sign up to set email alerts
|

The role of consumer innovativeness and perceived risk in online banking usage

Abstract: PurposeThe purpose of this paper is to analyse how consumer innovativeness can be used as a variable to positively influence internet banking adoption both directly and reducing consumer perceived risk.Design/methodology/approachThe impact of innovativeness and risk on internet banking adoption has been tested through structural equation modelling techniques. The sample consists of 511 Spanish internet banking services users accessed through an internet survey. Risk has been measured as a formative construct.F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
143
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(162 citation statements)
references
References 90 publications
(118 reference statements)
17
143
0
2
Order By: Relevance
“…For example, 6-items measure Fashion innovativeness construct is adopted from the study of Park et al (2007). Six items measure Consumer innovativeness variable is adopted from the studies of (Goldsmith & Hofacker, 1991;Citrin et al, 2000;Park et al, 2007;Aldás-Manzano et al, 2009). Five items measure the Fashion involvement construct, is derived from the studies of (Belton & Clinton, 2007;Cardoso et al, 2010).…”
Section: Instrument and Measuresmentioning
confidence: 99%
“…For example, 6-items measure Fashion innovativeness construct is adopted from the study of Park et al (2007). Six items measure Consumer innovativeness variable is adopted from the studies of (Goldsmith & Hofacker, 1991;Citrin et al, 2000;Park et al, 2007;Aldás-Manzano et al, 2009). Five items measure the Fashion involvement construct, is derived from the studies of (Belton & Clinton, 2007;Cardoso et al, 2010).…”
Section: Instrument and Measuresmentioning
confidence: 99%
“…Individuals ' personalities would refl ect their attitudes and perceptions about online banking. Research on adoption of online banking has investigated different individual personality dimensions like self-effi cacy and use of technology; 56,57 consumer innovativeness trait 19,39 and cultural differences may affect the consumers ' ability to take risk. 58 …”
Section: Conceptual Framework Online Banking and Consumer Personalitymentioning
confidence: 99%
“…Put together, the reduction of costs and increased customer satisfaction makes the logic of the Internet compelling [19]. The internet banking is a new type of information system that uses the innovative resources of the Internet and WWW to enable customers to effect financial activities in virtual space [20] and [21]. A study of US retail banking sector showed that the transaction costs of telephone banking are only 40 percent of those of providing the same service via physical branches [22].…”
Section: Problem Statementmentioning
confidence: 99%